PERANCANGAN "THE ADVENTURE OF TWINNY" UNTUK ANAK USIA 4-6 TAHUN GUNA MEMBERIKAN PENGALAMAN BELAJAR YANG EFEKTIF DAN MENYENANGKAN - Inez Zaneta Aprilia; Marina Wardaya (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2024)
Abstract Designing "The Adventure of Twinny" for children aged 4-6 years to provide an effective and fun learning experience. Early childhood education has a very important role for the development of children. Early childhood has a Golden Age at the age of 0-6 years which begins with physical, motor and language development. However, every child has problems, especially in terms of education and learning methods. The problem faced by early childhood is that they have difficulty in remembering, reading, spelling, and writing. As well as having difficulty in counting material caused by internal factors and external factors. The cause of internal factors is that the child has difficulty in counting, and the cause of external factors is parents who teach children to count with monotonous methods, making it difficult for children to understand, and the counting material taught is not suitable for early childhood. The purpose of this design is to design a children's storybook "The Adventure of Twinny" with a focus on interesting concepts and visual design elements for children aged 4-6 years with the aim of providing an effective, interactive and fun learning experience. This design method uses a qualitative method by collecting literature data sources, as well as interviews with parents (mothers), and children's book illustrators. TThe results of the design are in the form of a storybook design concept supported by valid literature data sources and illustrative design of interesting visual elements with the aim of providing an interactive learning experience, effective education, and fun for children aged 4-6 years which aims to educate children about the names of 5 types of vegetables, helping children in reading, spelling, writing, and counting by using objects in the form of vegetable characters. Keywords: book design, illustration, education, children, early childhood  Abstrak Perancangan “The Adventure of Twinny” Untuk Anak Usia 4-6 Tahun Guna Memberikan Pengalaman Belajar yang Efektif dan Menyenangkan. Pendidikan anak usia dini berperan penting dalam tumbuh kembang anak, terutama pada masa keemasan mereka (Golden Age) di usia 0-6 tahun, yang ditandai dengan perkembangan fisik, motorik, dan bahasa. Anak usia dini memiliki permasalahan terutama dalam hal pendidikan dan metode pembelajaran yang monoton. Permasalahan tersebut seperti, kesulitan dalam mengingat, membaca, mengeja, menulis dan berhitung, baik disebabkan oleh faktor internal maupun eksternal. Tujuan dari perancangan ini adalah merancang buku cerita anak “The Adventure of Twinny” dengan fokus pada konsep dan unsur desain visual yang menarik untuk anak usia 4-6 tahun dengan tujuan memberikan pengalaman belajar yang efektif, interaktif dan menyenangkan. Metode perancangan ini menggunakan metode kualitatif dengan mengumpulkan sumber data literatur, serta wawancara kepada orang tua (ibu), dan ilustrator buku anak. Hasil perancangan berupa konsep desain buku cerita yang didukung sumber data literatur yang valid dan desain ilustrasi unsur visual yang menarik dengan tujuan memberikan pengalaman belajar interaktif, edukasi efektif, dan menyenangkan bagi anak usia 4-6 tahun yang bertujuan untuk mengedukasi anak tentang nama 5 jenis sayuran, membantu anak dalam membaca, mengeja, menulis, dan berhitung dengan menggunakan benda berbentuk karakter sayuran.Kata kunci: desain buku, ilustrasi, edukasi, anak, usia dini